Distribution of plasma cells and other cells containing immunoglobulin in the respiratory tract of normal man and class of immunoglobulin contained therein. Issue 2 (April 1976) - Soutar, C A
Abstract : The anatomical distribution of plasma cells and other cells containing immunoglobulin in the respiratory tract, and the relative proportions of the immunoglobulin classes have been estimated on necropsy tissues from nine adult human subjects without respiratory disease, five non-smokers and four smokers, none of whom had cough or sputum. Cell counts on multiple sections stained by immunofluorescent methods for the presence of immunoglobulin were carried out on the upper trachea, main bronchus, and lower lobe bronchus. Cells containing immunoglobulin were found mostly in the submucous glands but were also present in the lamina propria of the tracheal and bronchial epithelium. These cells were present in the greatest concentration in the main bronchus and were always present in the lobar bronchus and, in most subjects, in the upper trachea. The cells were not always present round small bronchi and bronchioles and were virtually absent from alveolar walls. Cells containing IgA were much more numerous than those containing other immunoglobulin classes in all subjects except one, in whom IgG and IgE cells were equally numerous. Two subjects appeared to be significantly different from the rest. One non-smoking subject had a marked deficiency of IgA cells at all sampling sites, and one smoker had a marked excess of IgA cells. In spite of these two subjects there was no significant difference between smokers and non-smokers except in the lobar bronchus where the smokers had significantly more IgA cells than the non-smokers.